El abc matemático: unidad didáctica para la comprensión de enunciados matemáticos en estudiantes de grado tercero (2016)
Subjects such as Spanish and mathematics are considered basic subjects and fundamental for the training in skills of students both in primary and secondary. This does not mean that the other areas that make up the academic curriculum They deserve less recognition and importance. However, the subjects previously named develop skills such as the capacity for inference, analysis, synthesis, deduction, induction, association and logical reasoning